Assessment of obsessive––compulsive disorder: review and future directions. (February 2011) - Benito, Kristen; Storch, Eric A
Careful evaluation of obsessive––compulsive disorder (OCD) is critical owing to its under-recognition, difficulty ascertaining accurate diagnoses and the need for detailed treatment planning. We review current methods for the assessment of OCD in adults, including unstandardized clinical interviews, standardized diagnostic and other clinical interviews, patient- and family-report measures, and brief or web-based screening measures. Depending upon the question of interest, clinicians and researchers may select from these measures to best assess obsessive––compulsive symptoms in multiple settings. Current research regarding the assessment of OCD has focused on the underlying symptom dimensions, suggesting that each symptom dimension may be associated with different etiology and require tailored treatment. In the future, research may show that effective assessment of OCD involves identification of relevant symptom dimensions to facilitate the choice of appropriate treatment.